Separation and characterization of carbonaceous particulate (soot and char) produced from fast pyrolysis of coal in inert and CO2 atmospheres. (1st August 2017) - Apicella, B.; Senneca, O.; Russo, C.; Heuer, S.; Cortese, L.; Cerciello, F.; Scherer, V.; Schiemann, M.; Ciajolo, A.
Graphical abstract: Highlights: Effect of inert and CO2 -rich atmospheres on the fast pyrolysis of coal. Separation method of soot and char from carbon particulate formed in coal pyrolysis. Structural characterization of coal-derived soot and char. Soot and char formation mechanisms. Abstract: In a previous work [Heuer et al., 2016] a large production of a fluffy carbon-rich material was observed to accompany the char formed during the early stages of a medium rank (bituminous) coal pyrolysis in a drop tube furnace (1573 K, residence times < 130 ms). This peculiar material was found to be much more abundantly formed in CO2 than in N2 flow. SEM analysis showed that it contains a large portion of submicron soot-like particles mixed with particles of tenths of microns in size with the typical char morphology. The present work reports on the separation of the two differently sized fractions produced in CO2 and N2 flow and their subsequent analysis. The separation was performed dispersing the material in ethanol by ultrasonic mixing, followed by settling, and decanting to produce top and bottom products enriched in the fine and coarse particle fractions, respectively. The procedure was repeated several times and the size separation effectiveness was checked by SEM and laser granulometry sizing. Thermogravimetry, elemental and spectroscopic analysis were applied to the coarse and fine fractions to provide insights on their structural features. The fine soot particulate was almost ash-free, suggesting that its formation occurs in the gas phase, as typically soot does, while the coarse fraction presented significant residues of coal inorganic matter typical of char. Both fine and coarse particulate resulted less reactive, and somewhat smaller in size, when produced in CO2 in comparison to N2 /Ar pyrolysis conditions. Their lower reactivity is associated with higher aromaticity and structural order as well as with a lower presence of hydrogen and aliphatic functionalities.